Glocal Mobility Model: Promoting Language Learning and Intercultural Competence in Open Education - Nik Aloesnita, Nik Mohd Alwi (MQA, 2016)
Interaction is deemed important in second/ foreign language teaching and learning because it encourages negotiation for meaning and interactional feedback (Philp, Adams & Iwashita, 2014). Bowles and Adams (2015) argued for more studies on learner-learner interaction due to the setting in the non-native countries in which the non-native/non-native speakers (NNSs/NNSs) of English typically engage in the interaction among themselves more frequently than they do with the native speakers. Additionally, studies have shown that online interaction may promote engagement in the learning and acquisition of the language (Adams, Nik & Newton, 2015). Hence, more studies should be conducted to examine the potential of open education in the digital globalized age. Thirty undergraduate learners in Malaysia and Thailand while thirteen undergraduate learners in Japan participated in the current study. The learners in Malaysia and Thailand met via text chat and discussed issues pertaining to the lack of communication skills in the graduates in both countries. Meanwhile, the learners in Malaysia and Japan made use of several online tools and worked collaboratively to complete a presentation on workplace issues pertinent to both countries. The findings illustrate that despite vast differences in the learners’ proficiency levels, they were able to communicate and complete the project. Interestingly, the findings also show that interaction between the NNSs/NNSs led to intercultural appreciation. Finally, challenges faced by the teaching instructors and learners in online interaction were evident.